Depathologising Recognition: Ethical Scaffolding, Openness to Indeterminacy, and Diachronicity - Pierosara, Silvia (Itinerari, 2023)
Recognition can serve as a moral principle, directed at understanding and promoting the human capacity to criticise and transform frames of signification and normativity. For it to be so directed, recognition should be enforced and scaffolded by other principles with which cooperation within moral reasoning can be established. Taking my cue from several of Axel Honneth’s reflections, I argue for an intersection of recognition and autonomy that leaves room for indeterminacy and diachronicity. First, I discuss the possibility of regarding recognitional phenomena as being non-immediate; second, I intersect the dynamics of recognition with those of autonomy by showing that recognition should be scaffolded by a precise definition of ‘autonomy’; third, I propose leaving recognition undetermined and undefined so that the human capacity to criticise, create, and respond to change can be valued. Being recognised as autonomous is thus equivalent to being deemed capable of co-authoring one’s own life and its meanings.